Belajar tidak lagi membosankan di TERASIK (Tempat belajar asik) - Elda Febriana; Bengkel Ginting (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Learning is important and cannot be separated from one's life, because in daily activities learning is like a unit that is bound by every person, both from an early age to old age. Learning is a positive activity to change or improve one's behavior, attitude to personality, not infrequently learning is also used as an effort to increase knowledge. Learning can be done anywhere and by anyone, learning is not only obtained through formal education. On the other hand, informal learning activities can also be carried out, for example studying at home. Today the effectiveness of learning can increase if individuals live it happily. Children are judged to get bored quickly with monotonous learning. To change this, there is one way that can be done, namely introducing new methods of learning. Learning on the terrace of the house with a child-friendly concept can be a solution. A similar thing was experienced by a group of children in the Ban Rejo hamlet, they experienced problems related to learning. They think learning is boring. Because of the problems above, executor provide services using the groupwork intervention method to restore the social functioning of the group.